2012
DOI: 10.24220/2318-0897v20n3/4a582
|View full text |Cite
|
Sign up to set email alerts
|

Machined titanium disc decontamination using photodynamic therapy: an in vitro study

Abstract: ObjectiveThis study investigated less invasive protocols that do not injure peri-implant tissues during implant surface decontamination and evaluated, in vitro, the efficacyof microbiological decontamination of machined surface titanium discs with photodynamic therapy.MethodsForty eight titanium disc contaminated with 10μL of a Streptococcus sanguinis suspension were randomly divided into groups: 1) titanium disc contaminated with Ss (titanium disc suspension) without treatment; 2) titanium disc suspension rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Another study was conducted by Biondi Filho et al in which the discs were contaminated with Streptococcus sanguinis suspension. (28) The results showed that CHX was very beneficial, and interestingly, microbial reduction in the methylene blue group alone was more than that in the aPDT-treated group. (28) In the cited study, the samples were contaminated with 10 µl of microbial suspension for one hour.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Another study was conducted by Biondi Filho et al in which the discs were contaminated with Streptococcus sanguinis suspension. (28) The results showed that CHX was very beneficial, and interestingly, microbial reduction in the methylene blue group alone was more than that in the aPDT-treated group. (28) In the cited study, the samples were contaminated with 10 µl of microbial suspension for one hour.…”
Section: Discussionmentioning
confidence: 92%
“…(28) The results showed that CHX was very beneficial, and interestingly, microbial reduction in the methylene blue group alone was more than that in the aPDT-treated group. (28) In the cited study, the samples were contaminated with 10 µl of microbial suspension for one hour. Also, the discs were much smaller than the discs used in the present study, and accordingly, decontamination with laser showed better results due to the higher concentration of irradiation in a smaller surface area.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation